Biodiversity modelling in practice - predicting bird and woody plant species richness on farmlands. Issue 1 (1st January 2020) - Sybertz, Janine; Matthies, Sarah; Schaarschmidt, Frank; Reich, Michael; von Haaren, Christina
ABSTRACT: In light of decreasing species richness on farmland and an increasing awareness of biodiversity issues among customers and food companies, concepts and models to evaluate and enhance farmland biodiversity are greatly needed. It is important that the models are easy to apply as they have to be utilized by practitioners such as farmers and their consultants. In this study, simple but valid predictors were identified to rapidly assess the species richness of birds and woody plants in hedgerows, an important farmland landscape element. Hedgerows were sampled in seven agricultural landscapes throughout Germany. By means of automatic model selection procedures, linear regression models were estimated to predict bird and woody plant species richness. Cross validation procedures were carried out in order to visualize model selection uncertainty and estimate the prediction error. Due to a rather high prediction error, the model for plants can only be recommended for use when field work is not feasible. The model for birds, however, explained 70.8% of the variance in species numbers. It may help farmers, food companies and nature conservation agencies to rapidly evaluate bird species richness in hedgerows on farmland and to identify potentials and appropriate measures for enhancing it.